Determination of the Type of Child Development Disorders with the Dempster Shafer Method - Sinulingga, Checi Lia sari; Yustika, Fuzy; Pasaribu, Tio Ria (International Journal of Informatics, Economics, Management and Science; Vol 3 No 1 (2024): IJIEMS (January 2024), 2024)
Children are the most beautiful gift for parents. These awards sometimes have deficiencies or many of them experience disturbances during their development. There are various kinds of developmental disorders that children suffer from, including: autism, ADHD, ADD, speech delay, Asperger's syndrome, and Taurette's syndrome. In Indonesia, 5% of the school-age population to some degree suffers from developmental disorders, one of which is Hyperactivity Disorder. Hyperactivity Disorder is experienced more by boys than girls, with an estimate of 2-4% for girls, and 6-9% for boys aged 6-12 years. One of the real challenges nowadays is the high cost to do a health check. So that many children are not brought by their parents to undergo examinations because of limited funds. In addition to funding, the lack of experts or specialists in the field of child health is also a factor for parents' reluctance to have their children examined. Situations that often occur in areas, especially those far from the city center. In this study, the Dempster Shafer method will provide an initial diagnosis and classification of the types of child development disorders into several classifications such as in the case of Hyperactivity Disorder, with the categories of Hyperactivity, Impulsivity and Inattention. Based on the results of manual calculations using the Dempster Shafer, a presentation value of 0.6 is obtained leading to inclusive disease. It is also a factor that parents are reluctant to have their children examined. Situations that often occur in areas, especially those far from the city center. In this study, the Dempster Shafer method will provide an initial diagnosis and classification of the types of child development disorders into several classifications such as in the case of Hyperactivity Disorder, with the categories of Hyperactivity, Impulsivity and Inattention. Based on the results of manual calculations using the Dempster Shafer, a presentation value of 0.6 is obtained leading to inclusive disease. It is also a factor that parents are reluctant to have their children examined. Situations that often occur in areas, especially those far from the city center. In this study, the Dempster Shafer method will provide an initial diagnosis and classification of the types of child development disorders into several classifications such as in the case of Hyperactivity Disorder, with the categories of Hyperactivity, Impulsivity and Inattention. Based on the results of manual calculations using the Dempster Shafer, a presentation value of 0.6 is obtained leading to inclusive disease. and Intention. Based on the results of manual calculations using the Dempster Shafer, a presentation value of 0.6 is obtained leading to inclusive disease. and Intention. Based on the results of manual calculations using the Dempster Shafer, a presentation value of 0.6 is obtained leading to inclusive disease.